Influence of voltage asymmetry on energy characteristics of milk pumps - Sinyavsky, O.; Savchenko, V.; Prudnikova, N.; Fedoseykin , V. (Energy and Automation, 2025)
Voltage deviations and asymmetry have the greatest impact on the electric drives of production machines and mechanisms. Voltage asymmetry leads to losses that have an electromagnetic and technological component. Studies on the influence of voltage asymmetry on the technological characteristics of working machines and mechanisms have shown that with voltage asymmetry their productivity decreases. However, there are no studies on the influence of voltage asymmetry on the energy characteristics of milk pumps. The purpose of the study is to establish the influence of voltage asymmetry on the energy characteristics of milk pumps. With voltage asymmetry, constant and variable losses in an asynchronous electric motor change. It is advisable to conduct an energy assessment of the electric drive of a milk pump based on specific electricity consumption. The influence of voltage asymmetry on the energy characteristics of a centrifugal milk pump was studied. The dependence of the specific electricity consumption on the change in the rigidity of the mechanical characteristic of the electric motor, which is due to voltage asymmetry, was obtained. It was established that with voltage asymmetry, slip and power losses increase. As a result, specific electricity losses in milk pumps increase. Key words: milk pump, voltage asymmetry, power, pump performance, specific electricity consumption